Use of nominal address terms in Spanish movie - Abdul Rahman, Ummi Syakirah (2020)
Language is a way of expressing meaning in context. Aside from carrying the meaning of the words uttered, human conversation includes information about the interlocutors such as their origin and social class, their relationship, and often, it signals information of the setting in which the conversation take place. This is because the interlocutor’s selection of words is influenced by these elements. Address term is one of the words that are selected by the interlocutors accordingly in a conversation. A mastery of address terms is fundamental in order to grasp the insight of social concepts and human relationship (Yang, 2010). Solely, learning basic grammar rules of a language is insufficient. Speakers need to understand the rules of language use which is address terms in particular and know how to use it practically. In response to this matter, this study attempts to explain on the use of AT and examine some significant elements pertaining its use. This objectives of the study were to explain the types of address terms used by characters in a movie, to investigate the function of the address term and to analyse the social factors that influence the use of these terms. The research design was non-experimental descriptive qualitative by utilizing content analysis and the data was collected by finding the utterances of these address terms in a Spanish movie entitled No Se Aceptan Devoluciones (No Instructions Included). Based on some predetermined criteria, this Spanish movie was selected because it is relevant to the study. It closely mirrors social reality by illustrating realistic characters and life situation. The characters in this movie use colloquial Spanish language with a realistic fiction genre that depicts natural everyday life of Spanish society. The data were analysed using Wardhaugh’s (20060 theory of address terms. The findings of the study revealed that the characters in the movie employed five out of seven types of address terms proposed by Wardhaugh (2006) which were first name, title, title plus last name, pet name and kinship term. Among all the address terms used, first name scored the highest number of occurrences while title plus last name scored the lowest. Besides, it was found that the most prevailing function is to show intimacy while the least prevailing function is to show respect. The analysis also shows that the most dominant social factors is degree of intimacy and the least dominant social factors is occupational hierarchy. It is hoped that this study has highlighted some insights in language studies that could be applied by language users, learners and educators in the efforts of achieving better communication for social harmony.